2021
DOI: 10.1021/acsami.0c20978
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Electrode–Electrolyte Interfaces in Lithium-Ion Batteries Using Molecularly Engineered Functional Polymers

Abstract: Electrode−electrolyte interfaces (EEIs) affect the rate capability, cycling stability, and thermal safety of lithium-ion batteries (LIBs). Designing stable EEIs with fast Li + transport is crucial for developing advanced LIBs. Here, we study Li + kinetics at EEIs tailored by three nanoscale polymer thin films via chemical vapor deposition (CVD) polymerization. Small binding energy with Li + and the presence of sufficient binding sites for Li + allow poly(3,4-ethylenedioxythiophene) (PEDOT) based artificial coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…[6,10] This process not only leads to the generation of protons that can further induce a decomposition of lithium hexafluorophosphate (LiPF 6 ) to form hydrofluoric acid (HF), [11][12][13] but also causes the formation of spinel-like and rock salt-like phases at the cathode/electrolyte interphase (CEI). [14][15][16][17][18] Moreover, the generated TM ions and HF can crossover and exert side effects on the performance of Gr anodes. [19][20][21] In addition, EC molecules can also easily react with the oxygen released from high-Ni cathodes at elevated temperatures, leading to a catastrophic heat release and eventual safety hazards.…”
mentioning
confidence: 99%
“…[6,10] This process not only leads to the generation of protons that can further induce a decomposition of lithium hexafluorophosphate (LiPF 6 ) to form hydrofluoric acid (HF), [11][12][13] but also causes the formation of spinel-like and rock salt-like phases at the cathode/electrolyte interphase (CEI). [14][15][16][17][18] Moreover, the generated TM ions and HF can crossover and exert side effects on the performance of Gr anodes. [19][20][21] In addition, EC molecules can also easily react with the oxygen released from high-Ni cathodes at elevated temperatures, leading to a catastrophic heat release and eventual safety hazards.…”
mentioning
confidence: 99%
“…Synchrotron-based techniques have been demonstrated to be powerful for operando battery studies. 19,20 Recently, Charalambous et al demonstrated the effectiveness of synchrotron-based X-ray diffraction (XRD) to detect lateral heterogeneities in lithium intercalation 21 and the evolution of lithium plating on graphite under fast charging conditions for a single cell over an extended cycle life. 22 Here, we perform a synchrotron-based lateral XRD mapping technique to measure plated Li on the Cu anode in anode-free cells with a similar procedure.…”
Section: Spatial Maps Of LI Distribution In Anode-free Cellsmentioning
confidence: 99%
“…Fig. 2 c compares the cycling stability of the two types of coin cells tested between 3.0 V – 4.5 V at room temperature (20 °C) at a C-rate of C/2 [3] . The capacity degradation of the two types of cells almost overlapped with each other, suggesting that the casing window had a negligible effect on the cycling stability.…”
Section: Methods Validationmentioning
confidence: 99%